Ahmed drainage valve surgery in the various forms of glaucoma in children - T. N. Iureva; O. I. Mikova; N. V. Volkova; I. V. Pomkina (Oftalʹmologiâ, 2016)
Actuality. Glaucoma is an expected complication of many congenital eyeball malformations, such as aniridia, microcornea, consequence of mesenchymal dysgenesis with the formation of Frank — Kamenetz or Rieger syndromes, on the background of postoperative aphakia or after implantation of the «artificial iris — IOL» complex in children with congenital aniridia. Antihypertensive drug therapy gives only a partial effect in these cases, but excessive post-operative scarring nullifies results of fistulizing surgery even with antimetabolites and requires, as a rule, of numerous surgical procedures with transient hypotensive effect and following inexorable decrease of visual function.Purpose. To assess the level and duration of the hypotensive effect and nature of the complications of Ahmed valve system implantation with various forms of glaucoma in children.Patients and methods. Retrospective analysis of the effectiveness of implanted Ahmed valve system in 22 children (27 eyes) from 2008 to 2014 was made. 17 of them had previous antiglaucomatous surgery, such as trabeculectomy, cryo- and laser destruction of ciliary body. In 4 patients with congenital aniridia after implantation of the complex «artificial iris — IOL» and in one patient with postoperative aphakia the drainage surgery was the primary intervention and performed on both eyes.Results. As a result of Ahmed valve implantation in 25 cases the IOP compensation was achieved within 15‑17 mmHg by Maklakov, 23 — without additional medication. In 6 % of cases, the formation of fibrous capsule around the base of the drainage was the indication for needling, which was accompanied by a successful activation of the drainage system. In one case, the epithelial ingrowth with occlusion of the capillary was observed in the course of the wound channel, it required the implantation of a second drainage in free quadrant of the eyeball. Reduced visual function after surgery was observed in only one patient as a result of hemorrhagic choroidal detachment, the cause of it can bea post-operative hypotension and absence of forming structures on the background of aphakia and avitria.Conclusion. Thus, the implantation of the Ahmed valve drainage is sufficiently safe and effective method of surgical treatment of glaucoma in children and can be recommended as the operation of choice in such forms as secondary aphakic glaucoma and glaucoma in children with aniridia after implantation of the «artificial iris — IOL complex».